PENERAPAN MODEL PETA KONSEP TIPE NETWORK TREE MENGGUNAKAN MEDIA VISUAL UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA MATA PELAJARAN IPA KELAS IV SDN 3 JANGKAR KABUPATEN SITUBONDO TAHUN PELAJARAN 2015/2016 - Eko Hadi Purwanto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2015)
The learning model of map concept type network tree by using visual media (image of puzzle) is way to show the concepts and propositions in learning science. By self-making of the map concept, pupils are able to “notice” the learning material clearer and more meaningful. While, the visual media (image of puzzle) is like pieces image which is used to distribute message (learning material) so that it attracts pupil’s attention, interest, thought and feeling in learning activity to achieve the goal of learning. The subject of this research are pupils grade IV, uneven semester of public primary school SDN 3 Jangkar, district Situbondo which consist of 21 pupils, 12 girls and 9 boys. Type of this research is classroom action research. It is measured by the ARCS motivation questionnaire. The cycle I is average of ARCS pupil’s motivation aspect of 2,21 which is categorized as quite good. The cycle II is average of ARCS pupil’s motivation aspect is 3,06 which is categorized good. The increasing of ARCS’s motivation is 0,85. The increasing from cycle I to cycle II is 17, 14% and the complexness is 32%. Based on the analysis result it can be conclude that the application model of map concept learning type network tree by using visual media (images of puzzle) is able to increase the motivation and learning outcome of the pupils of grade IV, public primary school of SDN Jangkar district of Situbondo